2008
DOI: 10.1208/s12249-007-9013-9
|View full text |Cite
|
Sign up to set email alerts
|

Amorphization Alone Does Not Account for the Enhancement of Solubility of Drug Co-ground with Silicate: The Case of Indomethacin

Abstract: Abstract. The solubility advantage of indomethacin amorphized by co-grinding with Neusilin US2 in various media was investigated. Physical mixtures of γ-indomethacin and Neusilin US2 (in the ratios 1:1, 1:4 and 1:5) were amorphized at room temperature employing 75% RH in a porcelain jar mill using zirconia balls. The crystallinity of the samples was determined using ATR-FTIR and PXRD. The solubility and dissolution profiles of co-ground powders and crystalline counterparts were evaluated in 0.1 N HCl, water an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 32 publications
2
29
1
Order By: Relevance
“…IN (pKa of 4.5) exhibits pH-dependent solubility, which increases as a function of higher pH (acidic to neutral/alkaline: 1.5 µg/mL at pH 1.2 and 105.2 µg/mL at pH 7.4). IN displayed a solubility of 0.64 ± 0.02 mg/mL in phosphate buffer at pH 7.0, which is consistent with previously reported data [32, 33]. Additionally, the solubility of IN was increased by ~5 and ~6-fold with 5% w/v HPβCD and RMβCD in phosphate buffer at pH 7.0.…”
Section: Discussionsupporting
confidence: 91%
“…IN (pKa of 4.5) exhibits pH-dependent solubility, which increases as a function of higher pH (acidic to neutral/alkaline: 1.5 µg/mL at pH 1.2 and 105.2 µg/mL at pH 7.4). IN displayed a solubility of 0.64 ± 0.02 mg/mL in phosphate buffer at pH 7.0, which is consistent with previously reported data [32, 33]. Additionally, the solubility of IN was increased by ~5 and ~6-fold with 5% w/v HPβCD and RMβCD in phosphate buffer at pH 7.0.…”
Section: Discussionsupporting
confidence: 91%
“…Yang et al (12) showed a slower dissolution rate of prednisone compared to its crystalline form. An improvement in the dissolution rate and bioavailability of indomethacine by interaction with silica was reported by Watanabe et al (13) Most of the previous studies on cogrinding reported a dramatic increase in the dissolution rate of drug amorphized by cogrinding technique with carrier (14,15). The product obtained from the cogrinding process can be packaged into sachets as powder form with pharmaceutically acceptable excipients.…”
Section: Introductionmentioning
confidence: 78%
“…Therefore, it is important to compare release rates of physical mixtures with coground samples to explore advantages of coground samples over simple physical mixtures. The physical mixtures of theophylline with various concentrations of magnesium stearate (1%, 3%, 5%, and 10%, w/w) were prepared at different mixing times (1,5,15, and 30 min), and the results of drug release from these formulations were presented in Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
“…Similar dissolution behavior has also been observed for indomethacin-Neusilin amorphous complexes. 25 Crystalline Sulindac did not show any appreciable improvement in dissolution or solubility when Neusilin was added to the dissolution media. Thus, the presence of Neusilin cannot explain the increased plateau concentration observed for the amorphous complexes.…”
Section: Dissolution Of Amorphous Complex and Drug Product In 01 N Hclmentioning
confidence: 90%